Α‐Amylase Modulation: Discovery of Inhibitors Using a Multi‐Pharmacophore Approach for Virtual Screening. (11th October 2016) - Al‐Asri, Jamil; Gyémánt, Gyöngyi; Fazekas, Erika; Lehoczki, Gábor; Melzig, Matthias F.; Wolber, Gerhard; Mortier, Jérémie
Abstract: Better control of postprandial hyperglycemia can be achieved by delaying the absorption of glucose resulting from carbohydrate digestion. Because α‐amylase initiates the hydrolysis of polysaccharides, the design of α‐amylase inhibitors can lead to the development of new treatments for metabolic disorders such as type II diabetes and obesity. In this study, a rational computer‐aided approach was developed to identify novel α‐amylase inhibitors. Three‐dimensional pharmacophores were developed based on the binding mode analysis of six different families of compounds that bind to this enzyme. In a stepwise virtual screening workflow, seven molecules were selected from a library of 1.4 million. Five out of seven biologically tested compounds showed α‐amylase inhibition, and the two most potent compounds inhibited α‐amylase with IC50 values of 17 and 27 μm . The scaffold benzylideneacetohydrazide was shared by four of the discovered inhibitors, emerging as a novel drug‐like non‐carbohydrate fragment and constituting a promising lead scaffold for α‐amylase inhibition. Abstract : Sugar control : A computer‐aided method was developed to compile key ligand–enzyme interactions for α‐amylase inhibition and to use this information to identify novel drug‐like compounds that are able to specifically bind α‐amylase. Structure‐based functionalization of these small leads can facilitate the design of novel α‐amylase inhibitors toward new treatments for metabolic disorders such as type II diabetes and obesity.